Keanekaragaman Mikrob Fungsional Rizosfer Nanas dengan Berbagai Tingkat Produktivitas - Aditya Dyah Utami; Suryo Wiyono; Rahayu Widyastuti; Priyo Cahyono (Institut Pertanian Bogor, 2020)
Functional microbes of rhizosphere play important roles in nutrient transformation and controlling disease as well as in supporting plant growth and development. However, there is no study on the role of functional microbes on pineapple productivity. The purpose of this study was to investigate the abundance and diversity of soil functional microbes at different growth phases at two levels of productivity and their correlations to disease incidence. The research process included sampling of pineapple rhizospheric soil from vegetative and generative phases pineapples at low and high plant productivity sites, observations of disease incidence, and isolations of functional microbes. Functional groups of bacteria were Azotobacter, phosphate-solubilizing bacteria, potassium-solubilizing bacteria, antibiotics-producing bacteria, IAA-producing bacteria, and chitinolytic bacteria. The soil sampling method was simple randomized sampling at 6 locations with an area of each location ± 5 ha with a depth of 20 cm. Rhizosphere were taken in plants grown in high productivity area (>60tons/ha) and low productivity area (<60 tons/ha) in vegetative and generative phases. The results showed that potassium-solubilizing bacteria, chitinolytic bacteria, and IAA-producing bacteria were more abundant during the generative phase compared to those during vegetative phase. While Azotobacter, phosphate-solubilizing bacteria, and antibiotic-producing bacteria were more predominant during vegetative phase at various crop productivy. Total density of microbes was higher in soil with high crop productivity than that in soil with low crop productivity. The abundance of chitinolytic bacteria and IAA-producing bacteria had negative correlation with disease caused by Erwinia chrysanthemi and Phytophthora cinnamomi. Keywords: chitinolytic bacteria, growth phase, IAA, pineapple disease